Pengembangan Job Sheet Programmable Logic Controller (PLC) Berbasis Logo Softcomfort Untuk Kelas XII SMK Negeri 1 Pungging - Achmad Rijal Hidayat; Tri Rijanto (Pusat riset dan Inovasi Nasional, 2024)
This study aims to determine the level of feasibility assessed from the aspects of validity, practicality, and effectiveness of the PLC-based Logo Softcomfort Job Sheet. Development utilized the Research and Development (R&D) research method. This study employed a one-group pretest-posttest design and was conducted on 34 students of XII TITL 1 class. The research employed a validation instrument for the job sheet, with practicality assessed through student responses, and the effectiveness measured through the cognitive pre-test and posttest scores of students. The results indicate that the job sheet's validity yielded a rating of 94.19, categorized as